2004
DOI: 10.1111/j.1365-2109.2004.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen deficiency during somitogenesis causes centrum defects in red sea bream, Pagrus major (Temminck et Schlegel)

Abstract: Vertebral deformities in red sea bream, Pagrus major, remain serious obstacles to the improvement of seedling quality for its aquaculture. However, the causalities of the deformities remain unclear and prevention methods have not yet been established. In this paper, oxygen deficiency during somitogenesis was demonstrated to cause centrum defects (formerly called fused vertebrae in many cases), which are the major vertebral deformity in cultured red sea bream. An induction experiment of centrum defects was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Skeletal deformities represent one of the most important problems for aquaculture. Skeletal deformities in cultured fish might be caused by various factors, including nutritional imbalances (lysine, vitamin, tryptophan, phospholipid, unsaturated fatty acid) (Cahu, Zambonino Infante, & Takeuchi, ; Lall & Lewis‐McCrea, ), genetic factors (Silva, Cordeiro, Richard, Conceição, & Rodrigues, ) and environmental factors (salinity, photoperiod, dissolved oxygen, water current) (Fjelldal et al., ; Hattori et al., ; Kurokawa et al., ; Okamoto et al., ). In the present study, 34.22% of individuals had skeletal abnormalities, which is higher than that documented for other species, such as D. dentex (Koumoundouros, Divanach, & Kentouri, b), P. fulvidraco (Huang et al., ), T. ovatus (Zheng et al., ) and P. erythrinus (Boglione et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal deformities represent one of the most important problems for aquaculture. Skeletal deformities in cultured fish might be caused by various factors, including nutritional imbalances (lysine, vitamin, tryptophan, phospholipid, unsaturated fatty acid) (Cahu, Zambonino Infante, & Takeuchi, ; Lall & Lewis‐McCrea, ), genetic factors (Silva, Cordeiro, Richard, Conceição, & Rodrigues, ) and environmental factors (salinity, photoperiod, dissolved oxygen, water current) (Fjelldal et al., ; Hattori et al., ; Kurokawa et al., ; Okamoto et al., ). In the present study, 34.22% of individuals had skeletal abnormalities, which is higher than that documented for other species, such as D. dentex (Koumoundouros, Divanach, & Kentouri, b), P. fulvidraco (Huang et al., ), T. ovatus (Zheng et al., ) and P. erythrinus (Boglione et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…They include: (i) dislocation, fusion, shortening, deformation or lack of the centra (Hattori et al . ; Sawada et al . ); (ii) dislocation, compression, deformation, lack or extra formation of the haemal and neural arches and apophysis (Nguyen et al .…”
Section: Vertebrae Anomaliesmentioning
confidence: 99%
“…Furthermore, deformation can negatively impact fish growth, survival, swimming, food conversion, and susceptibility to stress and pathogens (Andrades et al 1996;Koumoundourous et al 1997;Boglione et al 2001). Though the rearing environment (e.g., temperature, salinity, water current, dissolved oxygen, and tank color) (Koumoundouros et al 1999(Koumoundouros et al , 2001Hattori et al 2004;Sfakianakis et al 2004;Okamoto et al 2009;Georgakopoulou et al 2010;Owen et al 2012), genetic factors (Ferguson and Danzmann 1998;Castro et al 2007;Ma et al 2014c), parasites and pesticides (Kusuda and Sugiyama 1981;Liang et al 2012;Liu et al 2012) can affect fish bone development, more and more evidence has demonstrated that nutritional factors during larval fish rearing can directly cause fish deformity (Andrades et al 1996;Afonso et al 2000;Cahu et al 2003a;Sandel et al 2010).…”
Section: Introductionmentioning
confidence: 99%